2003
DOI: 10.1002/chem.200390132
|View full text |Cite
|
Sign up to set email alerts
|

Structural Regulation of a Peptide‐Conjugated Graft Copolymer: A Simple Model for Amyloid Formation

Abstract: The self-assembly of peptides and proteins into beta-sheet-rich high-order structures has attracted much attention as a result of the characteristic nanostructure of these assemblies and because of their association with neurodegenerative diseases. Here we report the structural and conformational properties of a peptide-conjugated graft copolymer, poly(gamma-methyl-L-glutamate) grafted polyallylamine (1) in a water-2,2,2-trifluoroethanol solution as a simple model for amyloid formation. Atomic force microscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 59 publications
1
39
0
Order By: Relevance
“…The similarity among the different amyloid deposits and their ubiquity suggests that such structures might represent a generic form of the noncovalent packing of polypeptide chains (6,7,14). It may be possible that the aggregation into such well defined, nanoordered assemblies represents a state of an efficient minimal energy arrangement of polypeptide chains (15)(16)(17). Recent results have shown that fibrillar structures similar to amyloid fibrils are formed by sequences like poly(XGlyGlyYGly) (X, Y ϭ Val, Leu, or Ala), which are highly repeated in the hydrophobic domains of elastin (18,19).…”
Section: Charge Transport and Intrinsic Fluorescence In Amyloid-like mentioning
confidence: 99%
“…The similarity among the different amyloid deposits and their ubiquity suggests that such structures might represent a generic form of the noncovalent packing of polypeptide chains (6,7,14). It may be possible that the aggregation into such well defined, nanoordered assemblies represents a state of an efficient minimal energy arrangement of polypeptide chains (15)(16)(17). Recent results have shown that fibrillar structures similar to amyloid fibrils are formed by sequences like poly(XGlyGlyYGly) (X, Y ϭ Val, Leu, or Ala), which are highly repeated in the hydrophobic domains of elastin (18,19).…”
Section: Charge Transport and Intrinsic Fluorescence In Amyloid-like mentioning
confidence: 99%
“…The Aggresomal Bodies in Cardiomyocytes Are Amyloidphilic. In an attempt to define further the relationship of these electron-dense bodies to the amyloid-based degenerative diseases, we tested their ability to react positively to the amyloidphilic dye Congo red (26,27). Congo red-positive inclusions were abundant in CryAB R120G -transfected cardiomyocytes and were undetectable in cells that were transfected with either empty adenovirus or with CryAB adenovirus (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Nanoparticles having organic molecules such as peptides [8], oligonucleotides [9,10], and oligosaccharides [11] as building blocks have been utilized to form ordered and periodic arrangements of the nanoparticles. Especially, the structure of peptide assemblies can be controlled by external stimuli such as pH and solution composition [12,13]. Therefore, the functions of peptide-coated nanoparticle assemblies may be controlled by the stimulus induced rearrangement of the nanoparticles owing to the structural changes of the surface peptide chains.…”
Section: Introductionmentioning
confidence: 99%